2008
DOI: 10.1093/ajcn/87.2.362
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin status in morbidly obese patients: a cross-sectional study

Abstract: Low concentrations of vitamin B-6, vitamin C, 25-hydroxyvitamin D, and vitamin E adjusted for lipids are prevalent in morbidly obese Norwegian patients seeking weight-loss treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
211
2
15

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 273 publications
(242 citation statements)
references
References 45 publications
12
211
2
15
Order By: Relevance
“…It is well established that obesity is associated with vitamin D insufficiency. Our data confirm previous reports showing a high prevalence of vitamin D insufficiency in morbidly obese subjects (Carlin et al, 2006;Aasheim et al, 2008;Goldner et al, 2008;Lagunova et al, 2009). Our study has demonstrated that men had higher odds of vitamin D deficiency even after adjustment for the confounders season, age, current smoking and vitamin D supplements (model 2).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is well established that obesity is associated with vitamin D insufficiency. Our data confirm previous reports showing a high prevalence of vitamin D insufficiency in morbidly obese subjects (Carlin et al, 2006;Aasheim et al, 2008;Goldner et al, 2008;Lagunova et al, 2009). Our study has demonstrated that men had higher odds of vitamin D deficiency even after adjustment for the confounders season, age, current smoking and vitamin D supplements (model 2).…”
Section: Discussionsupporting
confidence: 91%
“…Women have relatively more body fat than men and store more fat in the gluteal-femoral region, while men typically store more fat in the visceral (abdominal) depot (Blaak, 2001;Hofso et al, 2009a). Some studies have found a higher prevalence of vitamin D deficiency among men than women (Aasheim et al, 2008;Lagunova et al, 2009). As vitamin D is a fat soluble vitamin that may potentially be sequestrated in adipose tissue (Wortsman et al, 2000), one could hypothesize that a gender difference in the prevalence of vitamin D deficiency is related to differences in the amount of body fat and/or its distribution.…”
Section: Introductionmentioning
confidence: 99%
“…The observation that obesity is associated with below-normal serum 25-hydroxyvitamin D concentrations and/or overt deficiency is not new; however, as obesity prevalence has grown, so have the number of reports in the literature regarding this phenomenon. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] Some of the most recent information about low vitamin D status and obesity comes from studies in bariatric surgery patients, reporting low preoperative circulating levels of 25-hydroxyvitamin D. [21][22][23][24][25][26][27][33][34][35][36][37][38] In fact, a recent systematic review of 14 studies with about 1500 patients undergoing bariatric surgical procedures confirmed that obese individuals have serum 25-hydroxyvitamin D levels below 80 nmol l À1 preoperatively. 39 Other investigators have reported that body mass index (BMI) 25,26,[40][41][42][43][44][45][46] and body fat 20,45,…”
Section: Methodsmentioning
confidence: 99%
“…One of these factors is body-mass index (BMI) that has been suggested to be negatively correlated with plasma/serum folate, although the findings are controversial [2][3][4][5][6][7][8][9][10][11][12][13][14]. For erythrocyte folate, another commonly used index of folate status, however, no such significant correlation are reported [4,5].…”
Section: Introductionmentioning
confidence: 99%